Resilience and Success Strategies: A Phenomenological Analysis of the Elements Affecting Retakers of Certified Public Accountant Licensure Examination in the Philippines - Augusto, Phoebe Mae; Borlasa, Keziah; Cosep, Jayrald; Francisco, Juddie; Yee, Angelo Joshua; Micabalo, Kingie; Cruspero Jr., Exequiel (Journal of Interdisciplinary Perspectives, 2025)
The journey to passing the Licensure Examination for Certified Public Accountants (LECPA) is especially challenging for retakers. This study explored the factors that influence the success of LECPA retakers from three private Higher Education Institutions (HEIs) in Cebu from 2018 to 2024. Using a qualitative phenomenological approach, in-depth interviews were conducted with fifteen alumni selected through purposive-random sampling. Data triangulation strengthened the credibility of the findings. Results revealed that successful retakers rely on disciplined learning strategies, strong personal well being, intrinsic motivation, and effective stress management. Support from family, peers, and academic mentors also played a crucial role, while financial stability—whether through family support or self-funding—helped sustain their preparation. The study concludes that LECPA success among retakers is shaped by holistic preparation and a supportive environment, areas often overlooked in existing research. Grounded in the Comprehensive LECPA Support Model (CLSM), the study recommends that institutions provide structured review programs, mentoring, wellness initiatives, and financial assistance to improve candidate readiness and enhance accountancy education outcomes.